Education on the Use of Vitamin A (Retinol) for the Prevention of Myopia in Adolescents in Gembleb Trenggalek: Edukasi Penggunaan Obat Vitamin A (Retinol) Untuk Pencegahan Penyakit Miopi Pada Remaja di Dusun Gembleb Trenggalek - Prasetyawan, Fendy; Saristiana, Yuneka; Salmasfattah, Novyananda; Savitri, Lisa; Herman; Kadir, Mujtahid Bin Abd (PELITA NUSA TENGGARA, 2025)
This community service program aimed to increase adolescents' awareness and knowledge regarding the role of Vitamin A (Retinol) in preventing myopia, particularly in rural areas such as Gembleb Village, Trenggalek. The activity was conducted on Saturday, May 3, 2025, in collaboration with the Government of Gembleb Village and supported by the Institute for Research, Community Service, and Publication (LP3M) of Universitas Kadiri. A total of 15 adolescents participated in the educational intervention, which included a pre-test, a lecture session, and a post-test evaluation. The results showed a significant improvement in participants’ knowledge about myopia and the importance of Vitamin A for eye health. Pre-test scores averaged lower compared to post-test results, with an average increase of 20–25 points. This finding suggests that structured education can effectively enhance health literacy among youth, particularly regarding nutritional prevention of visual disorders. These outcomes underscore the importance of continued community-based health education programs, especially in underserved areas, as a strategic effort to reduce the prevalence of preventable eye diseases